Hypoxylon Mammatum Ascospore Activity on Artificial and Saperda Inornata caused Bark Wounds of Populus Tremuloides - Noll, Richard K. (University of Wisconsin-Stevens Point, College of Natural Resources, 1982)
Greenhouse experiments were conducted in order to observe the role that wounds caused by the poplar gall Saperda (Saperda inornata) play in the infection of aspens (Populus tremuloides) by Hypoxylon canker (Hypoxylon mammatum). Observations were made using a scanning electron microscope (SEM). Unfortunately, the inoculation technique used proved inadequate, resulting in discontinuation of the insect phase of the study. However, there was one notable observation which might have some significance in relation to Hypoxylon canker. A necrosis, in the vascular cambium, was consistently observed surrounding the beetle eggs. This necrosis could prove significant by providing for specific microclimate requirements of the causal organism, and/or by decreasing the demonstrated inhibitory effects of aspen bark. After the insect phase of the project was discontinued, a second study was begun which utilized artificial bark wounds on potted aspens, in order to study the activity of ascospores of H. mammatum in relation to bark layer, wound age, and time interval after inoculation. Germinated ascospores, and their hyphae, were observed on all bark layers including the cortex, or green layer, which has been shown to have inhibitory effects on fungal growth. Wound age had little apparent effect on fungal activity, while more extensive mycelium development was visible with longer intervals after inoculation. Although superficial establishment of fungus was observed, only two trees of the 68 inoculated, became symptomatic. These observations suggest that the fungistatic properties which have previously been attributed to aspen bark.may be less important with respect to establishment of the fungus on living trees than was thought. Furthermore, in this study, H. mammatum exhibited a marked ability to live superficially without becoming pathogenic. Possibly, a unique combination of environmental factors may be required by either the host or the pathogen before the canker is induced.